Pengaruh Perbandingan Serbuk Santan dan Gula dalam Pembuatan Manisan Instan Beras Rendang terhadap Penerimaan Konsumen dengan Analisis Sensori Uji Pembeda - Risa Meutia Fiana; Wenny Surya Murtius; Aurian Ming (Green Engineering Society, 2019)
This research has been carried out in the Laboratory of Chemistry, Agricultural Biochemistry and Food Nutrition, Laboratory of Technology and Agricultural Process Engineering Faculty of Agricultural Technology Laboratory of Animal Husbandry Biotechnology Faculty of Animal Husbandry, and Laboratory of Tablet Faculty of Pharmacy in July to August 2018. The aims of this study was to determine the ratio of coconut milk and sugar to the characteristics of instant beras rendang flour and find out the best ratio in organoleptic instant beras rendang product with a differentiation test. This research method used a completely randomized design with 5 treatments and 3 replications, which treatments A (35% coconut milk powder : 15% sugar), B (30% coconut milk Powder : 20% Sugar), C (25% coconut milk Powder : 25% Sugar), D (20% Coconut Milk Powder : 30% Sugar), E (15% Coconut Milk Powder : 15% Sugar). Tests carried out included sensory analysis by differentiating test.